Kebijakan Pengelolaan Tambang dan Masyarakat Hukum Adat yang Berkeadilan Ekologis - Muchamad Ali Safaat; Aan Eko Widiarto; Fajar Laksono Suroso (The Constitutional Court of the Republic of Indonesia, 2019)
Permasalahan dalam penelitian ini adalah: pertama, bagaimana kebijakan pengelolaan sumber daya pertambangan berdasarkan undang-undang pertambangan mineral dan batubara? Kedua, bagaimana kebijakan pengelolaan sumber daya pertambangan perspektif masyarakat hukum adat yang berkeadilan ekologis? Metode penelitian ini menggunakan penelitian hukum normatif. Hasil penelitian ini menunjukkan bahwa, pertama, kebijakan pengelolaan sumber daya pertambangan berdasarkan undang-undang pertambangan mineral dan batubara saat ini hendaknya disesuaikan dengan putusan-putusan mahkamah konstitusi dan Undang-Undang Nomor 23 tahun 2014 tentang Pemerintahan Daerah dalam konteks perizinan. Pemerintah daerah provinsi sekarang ini mengambil alih kewenangan pemerintah kabupaten/kota untuk mengeluarkan izin tambang berdasarkan Undang-Undang Nomor 23 tahun 2014 yang sebenarnya masih bersifat semi sentralistik dan secara kewilayahannya dalam konteks tambang masih berada di kabupaten, sementara pemerintah provinsi sebagai wakil dari pemerintah pusat; kedua, Kebijakan pengelolaan sumber daya pertambangan perspektif masyarakat hukum adat yang berkeadilan ekologis terletak pada konsep kearifan masyarakat hukum adat dalam pengelolaan sumber daya alam, dalam hal ini tambang yang menjadi hak penguasaan negara. Terdapat hubungan timbal balik antara manusia dengan alam, dimana masyarakat hukum adat selalu menempatkan keseimbangan alam dalam pengelolaan lingkungan (participerend cosmisch), sehingga keadilan ekologis dapat dirasakan semua unsur alam, selain manusia.The problems in this paper are: first, what are the mining resource management policies based on mineral and coal mining laws? and second, how is the mining resource management perspective of the ecological justice community indigenous people? This research method uses normative legal research with the classification of secondary data including primary legal materials including legislation in the fields of mineral and coal mining, environmental protection and management, and regional government. Secondary legal material in the form of books and journals, while secondary legal material in the form of online news. Data analysis using qualitative juridical analysis. The results of this study are first, current mining resource management policies based on mineral and coal mining laws should be adjusted to the decisions of the constitutional court and Law No. 23 of 2014 concerning Regional Government in the context of licensing. The provincial government is currently taking over the authority of the district / city government to issue mining permits under Law No. 23 of 2014 which are actually still semi-centralistic and in the territory in the context of mines still in the district, while the provincial government is the representative of the central government; secondly, the policy of managing mining resources from the perspective of indigenous peoples with ecological justice lies in the concept of indigenous peoples’ wisdom in managing natural resources, in this case mining which is the state’s right of control. There is a reciprocal relationship between humans and nature, where customary law communities always place natural balance in environmental management (participerend cosmisch), so that ecological justice can be felt by all elements of nature, other than humans.